3D Concrete Printing: A Road Map for future of Automated Construction in India - Shaw, Raman; Maurya, Kundan Kumar; Maity , Damodar (PREPARE@u® | IEI Conferences, 2021)
3D concrete printing (3DCP) is the potential future of total automation in building and construction (B&C) industry. 3D concrete printing which works on the principle of additive manufacturing, has gained significant attention due to its promising benefits such as formwork free and efficient construction, high flexibility in architecture and customized design and minimized waste production etc. However, it is still at primitive stage due to lack of fundamental and comprehensive research on its various components such as printable materials, printed shape of structure, the forces acting on the structure and the printing methods itself. At first, this paper reviews the progress of 3DCP in B&C industry and academia across the world. The paper also highlights the current challenges in the path of use of 3DCP in Building & Construction sector particularly in India. Finally, the authors present their idea to accelerate the use of 3DCP in construction in India.